Climate change and harmful benthic microalgae - Tester, Patricia A.; Litaker, R. Wayne; Berdalet, Elisa (Harmful algae, 2020)
•Global SST increases of 0.4–1.4 °C by 2055 will promote growth rates of many BHABs.•Steep declines in growth are expected in areas where temperatures exceed 31 °C.•Migration to deeper, cooler habitats may provide protection from high temperatures.•Latitudinal range extensions to both the north and the south are expected.•Changes in salinity, pH, light are secondary to temperature in regulating BHABs.•Sentinel sites recommended for long-term monitoring to detect range extensions. Sea surface temperatures in the world’s oceans are projected to warm by 0.4–1.4 °C by mid twenty-first century causing many tropical and sub-tropical harmful dinoflagellate genera like Gambierdiscus, Fukuyoa and Ostreopsis (benthic harmful algal bloom species, BHABs) to exhibit higher growth rates over much of their current geographic range, resulting in higher population densities. The primary exception to this trend will be in the tropics where temperatures exceed species-specific upper thermal tolerances (30–31 °C) beyond which growth slows significantly. As surface waters warm, migration to deeper habitats is expected to provide refuge. Range extensions of several degrees of latitude also are anticipated, but only where species-specific habitat requirements can be met (e.g., temperature, suitable substrate, low turbulence, light, salinity, pH). The current understanding of habitat requirements that determine species distributions are reviewed to provide fuller understanding of how individual species will respond to climate change from the present to 2055 while addressing the paucity of information on environmental factors controlling small-scale distribution in localized habitats. Based on the available information, we hypothesized how complex environmental interactions can influence abundance and potential range extensions of BHAB species in different biogeographic regions and identify sentinel sites appropriate for long-term monitoring programs to detect range extensions and reduce human health risks.